Out-of-plane heat transfer in van der Waals stacks through electron–hyperbolic phonon coupling. Issue 1 (January 2018) - Tielrooij, Klaas-Jan; Hesp, Niels; Principi, Alessandro; Lundeberg, Mark; Pogna, Eva; Banszerus, Luca; Mics, Zoltán; Massicotte, Mathieu; Schmidt, Peter; Davydovskaya, Diana; Purdie, David; Goykhman, Ilya; et al.
Abstract Van der Waals heterostructures have emerged as promising building blocks that offer access to new physics, novel device functionalities and superior electrical and optoelectronic properties1–7 . Applications such as thermal management, photodetection, light emission, data communication, high-speed electronics and light harvesting8–16 require a thorough understanding of (nanoscale) heat flow. Here, using time-resolved photocurrent measurements, we identify an efficient out-of-plane energy transfer channel, where charge carriers in graphene couple to hyperbolic phonon polaritons17–19 in the encapsulating layered material. This hyperbolic cooling is particularly efficient, giving picosecond cooling times for hexagonal BN, where the high-momentum hyperbolic phonon polaritons enable efficient near-field energy transfer. We study this heat transfer mechanism using distinct control knobs to vary carrier density and lattice temperature, and find excellent agreement with theory without any adjustable parameters. These insights may lead to the ability to control heat flow in van der Waals heterostructures. Observation of an efficient out-of-plane energy transfer channel in van der Waals heterostructures, where charge carriers in graphene couple to hyperbolic phonon–polaritons on a picosecond timescale.